The Relationship Between Peer Support And Mental Health in Adolescents at Dwijendra Senior High School, Denpasar - Ni Made Ayu Sintya Astiti; Sukra Andini Ni Komang; Sri Sanjiwani Anak Agung (Yayasan Lentera Mitra Lestari, 2026)
Background: Adolescence is a developmental phase that is prone to mental health problems due to biological, psychological, and social changes. Peer support has an important role as a protective factor in helping teens manage stress, anxiety, and academic stress. However, there are still adolescents who experience mental health disorders even though they are in the school environment, so it is necessary to study the supporting factors that affect these conditions. Objective: This study aimed to find the relationship between peer support and mental health in adolescents at Dwijendra Senior High School, Denpasar. Methods: A quantitative design was used, with a cross-sectional approach. The research sample consisted of 163 first-level students, who were selected using stratified random sampling techniques. Data collection used a peer support questionnaire and the Mental Health Inventory (MHI-38). Data analysis was carried out using the Spearman Rank correlation test at a significance level of α = 0.05. Results: A value of p = 0.004 (p < 0.05) with a correlation coefficient of 0.223, indicating a positive and significant relationship between peer support and adolescent mental health. Conclusion: Peer support is significantly associated with adolescent mental health. The higher the support received from peers, the better the adolescent's mental health condition. These findings affirm the importance of strengthening the peer social environment as a promotive and preventive effort for mental health in schools.